Rare case of combined small cell lung cancer with adenocarcinoma and squamous cell carcinoma - Sameer AL Diffalha, MD; Saleh Hasan, BS; Maryam Tahmasbi, MD; Farah Khalil, MD (Elsevier, 2017)
Combined small cell lung cancer (cSCLC) is relatively unusual. We report a case of cSCLC in a 78-year-old man with no prior medical history who presented for evaluation of right upper lobe (RUL) lung mass. A CT scan showed a 3.0 × 2.5 × 2.3 cm RUL lung mass with mildly prominent mediastinal and hilar lymphadenopathy. A right thoracotomy with right upper lobectomy and lymphadenectomy was performed. Histological examination and immunohistochemical stains confirmed the diagnosis of combined small cell lung carcinoma (SCLC) with adenocarcinoma (AC) and squamous cell carcinoma (SCC) components.While there are available guidelines for treating SCLC, the optimal treatment for cSCLC which will improve prognosis has not been adequately determined. We report a very rare category of primary lung malignant neoplasm to represent our institution's experience in diagnosing and managing this type of rare case.